2020
DOI: 10.1093/cdn/nzaa158
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake and the Significance of Feeding in Qom Children of Northern Argentina

Abstract: Objectives The aims of this study were to explore the food consumption patterns of Qom preschoolers and to describe cultural domains about the significance of feeding in this indigenous population in northern Argentina. Design and methods This cross-sectional and mixed-methods study was conducted in 2016–2017 and focused on 160 preschoolers and their mothers in the village of Namqom. It used a closed questionnaire, three 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…We conclude that among the underlying causes of stunting in school children in Enrekang Regency are skipping breakfast or eating <3 times a day, food insecurity, lack of types of food due to too far access to markets, family income, and lack of nutrition awareness in the entire population. This research is not in line with a study by Olmedo et al [15] in Argentine children, it showed that there was no relationship between an energy-dense diet and the incidence of stunting.…”
Section: Relationship Between Children's Diet and Stunting Incidentscontrasting
confidence: 99%
“…We conclude that among the underlying causes of stunting in school children in Enrekang Regency are skipping breakfast or eating <3 times a day, food insecurity, lack of types of food due to too far access to markets, family income, and lack of nutrition awareness in the entire population. This research is not in line with a study by Olmedo et al [15] in Argentine children, it showed that there was no relationship between an energy-dense diet and the incidence of stunting.…”
Section: Relationship Between Children's Diet and Stunting Incidentscontrasting
confidence: 99%
“…In NamQom, integration into the market economy and a loss of traditional subsistence practices has led to rising rates of obesity and metabolic syndrome (Lagranja et al, 2015). NamQom has also been subject to pervasive food insecurity, poverty, childhood stunting, and a high prevalence of gastrointestinal and respiratory infections, including tuberculosis (Olmedo et al, 2020; Valeggia & Ellison, 2003; Valeggia & Tola, 1999). The health clinic in NamQom and its geographic location at the center of the community may facilitate frequent contact with healthcare providers trained in Western biomedical modes of care, resulting in widespread ideas about body size that are rooted in somewhat arbitrary clinical standards of “normal” and “healthy.” The existence of over nutrition alongside food insecurity and pathogenic burden, as well as the clinic's presence at the center of the community, may lead to frequent contact with both larger body sizes associated with cardio metabolic risks and thin body sizes associated with illness and food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Warna dan bentuk adalah bentuk dari menikamati sesuatu. Bentuk yang indah dan bagus akan dipersepsikan oleh seseorang yang melihatnya sehingga akan lebih tertarik [23]. Sama halnya dengan warna, warna yang indah juga akan mempengaruhi persepsi yang melihat untuk dapat dinikmati.…”
Section: Hasil Dan Pembahasanunclassified